Nonlinear hypoelastic analysis of reinforced concrete flat plate floors - Wang, Wenyuan (2010)
A three dimensional finite element model has been developed for nonlinear analysis of reinforced concrete flat plate structures in this study. A 3-D hypo-elastic orthotropic material model based on equivalent uniaxial strain concept for modeling the material properties of uncracked concrete and cracked reinforced concrete was proposed. Material property of uncracked concrete under multiaxial stress state was simulated by uniaxial stress-equivalent uniaxial strain relationships. The five-parameter strength surface proposed by Willam and Warnke (1975) was employed to determine the ultimate peak stress and peak strain. A new model describing the material properties of cracked reinforced concrete with multiple non-orthogonal cracks has been developed.